Maternal Adiposity is Associated with Fat Mass Accretion in Female but not Male Offspring During the First 2 Years of Life. Issue 3 (6th February 2020) - Heard‐Lipsmeyer, Melissa E.; Diaz, Eva C.; Sims, Clark R.; Sobik, Sarah R.; Ruebel, Meghan L.; Thakali, Keshari M.; Krukowski, Rebecca A.; Cleves, Mario; Børsheim, Elisabet; Shankar, Kartik; Andres, Aline
Abstract : Objective: This study investigated which antenatal and postnatal factors determine offspring adiposity during the first 2 years of life. Methods: Participants were mother and child pairs ( N  = 224). Offspring percent fat mass (%FM) was obtained using quantitative nuclear magnetic resonance at 11 time points between ages 0.5 and 24 months. Independent variables included race, age, gestational weight gain, first‐trimester %FM, delivery mode, gestational measures of resting energy expenditure, respiratory exchange ratio, physical activity, serum cytokines and lipids, and dietary intake for the mothers, as well as sex, birth weight and length, breastfeeding duration, and physical activity at age 2 years for the children. Linear mixed models were used to construct the best‐fitted models for the entire cohort and for each sex. Results: Maternal %FM ( P  = 0.006), high‐density lipoprotein (HDL) ( P  < 0.001), and breastfeeding duration ( P  = 0.023) were positively associated with female offspring adiposity, whereas maternal dietary fiber intake ( P  = 0.016) had a negative association. Birth weight ( P  = 0.004), maternal HDL ( P  = 0.013), and breastfeeding duration ( P  = 0.015) were all positively associated with male offspring adiposity. Conclusions: Antenatal and postnatal factors differentially impact male and female offspring adiposity during the first 2 years of life.